Experimental and Simulation Studies of Thermal Distribution on Modified Connector of Li-Ion Battery for Electric Vehicles Application - Agus Risdiyanto; Umar Khayam; Noviadi A. Rachman; Maulana Arifin (International Journal of Electrical and Computer Engineering (IJECE), 2016)
One of the several failure cases in electric vehicle could be occured at the Lithium-ion (Li-ion) battery connectors when loaded by high current. This failure caused by bad contact of connectors so that the contact resistance increase and lead to high power losses, overheating, and it can even cause a fire hazard. This paper presents a thermal distributions of  Li-ion battery connectors on different coating material in relation to the value of contact resistance. There were two test samples of modeled: copper connection without coating and copper connection with silver coating. Each sample was loaded by the DC current of 350A, and temperature at the connection was measured until steady state condition reached and simulated by Solidwork software. The results show that the temperature at the inside contact area was higher than the outside contact area of connection that appears caused by higher of the contact resistance. Both measurement and simulation results have same tendency that copper connection with silver coating having lower contact resistance, lower maximum temperature, and lower losses about 32 % than copper connection without  coating. Silver coating can be considered as other alternative to prevent overheating, high losses, and failure in Li-ion battery connector.